Understanding policy-based networking - Dave Kosiur (John Wiley & Sons, 2001)
This book offers a comprehensive overview of all the concepts, protocols, and systems we will need to understand before we can take advantage of this important new model of network management. It clearly explains how policy networking ties together diverse interface and devices, how to use it to offer a variety of user-demanded services, and how to go about deciding whether it's right for our organization.